Television Portrayals of the U.S. Intelligence Community Before and After 9/11. - Tanguay, Kimberly (My University, 2009)
The image of the intelligence community in the media has always been connected to the public's perception of the role and importance of those agencies. However, this changed after 9/11 and the emergence of television shows such as Alias and 24 brought the intelligence community and its agents back to life. The goal of our research was to examine the characteristics of both Alias and 24 that encouraged support for extralegal policies, reinforced fears of terrorism, and allowed viewers to see torture as an acceptable tool of government policy.
Color poster with text and images.
Keywords: 24 (Television program); Alias (Television program); Intelligence service--United States--Public opinion--History; Intelligence service--United States--On Television--History; Posters